Analisis Pengaruh Rasio Keuangan, Corporate Govermance, Dan Risk Based Capital Untuk Memprediksi Tingkat Kebangkrutan Di Perusahaan Batubara Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015-2019 - Risal Rinofah; Nina Yuliyanti (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims to examine and analyze the effect of Current Ratio, Debt Ratio, Return on Assets, Return on Equty, Net Profit Margin, Institutional Ownership, Managerial Ownership, Audit Committee, and Risk Based Capital on the Bankruptcy Rate of Coal Companies listed on the Indonesia Stock Exchange in 2015-2019. The population in this study are companies in the coal sector listed on the Indonesia Stock Exchange in 2015-2019. The sample of this study was 6 companies that suffered losses for two times in the time span of the study with a sampling technique that is pusposive sampling. This data is taken in the form of secondary data obtained from annual reports and company financial statements during the 2015-2019 research year. The method used consists of multiple regression analysis, classical assumptions, hypothesis testing (t test and f test) and test the coefficient of determination. The results of this research show that: (1) Current Ratio has no effect on the company's bankruptcy rate, (2) Debt Ratio has a positive effect on the company's bankruptcy rate, (3) Assets Return has no effect on the company's bankruptcy rate, (4) Return on equity does not affect the bankruptcy rate of the company, (5) Net Profit Margin has no effect on the bankruptcy rate of the company, (6) institutional ownership has no effect on the bankruptcy rate of the company, (7) managerial ownership has no effect on the bankruptcy rate of the company, (8) the audit committee does not affect the Bankruptcy Rate of the company, (9) Risk Based Capital has no effect on the Bankruptcy Rate of the company. Keywords: Current ratio, Debt Ratio, Return on assets, Return on Equty, Net Profit Margin, Institutional Ownership, Managerial Ownership, Audit Committee, Risk Based Capital, and Bankruptcy Rate.